Kajian Pendidikan Teknologi dalam Perspektif Tafsir Al-Qur’an - Indah Syafiqah Lubis; Asnil Aidah Ritonga; Ahmad Darlis (Instructional Development Journal, 2022)
The Qur'an has emphasized how important it is for Muslims to observe and contemplate the phenomena of nature and its universe. Muslims who develop science and technology are part of their faith in the Al-Qur'an. The Qur'an is a universal source of all knowledge, where we are required to continue to study and relate the Qur'an to our lives as proof of the faith of Muslims that the Qur'an is a way of life that is always relevant in every era. Technology in the verses of the Qur'an has been explained implicitly. So this study aims to examine how the perspective of interpretation of the verses of the Qur'an on technology. This research is a library research that focuses on the analysis or interpretation of content sourced from the Al-Qur'an, commentary books and journals.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//